2019
DOI: 10.1111/ans.15450
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography‐guided coil localization for video‐assisted thoracoscopic surgery of sub‐solid lung nodules: a retrospective study

Abstract: Background Wedge resection via video‐assisted thoracoscopic surgery (VATS) is the best choice for the diagnosis of sub‐solid lung nodules. Preoperative localization is utilized to increase the success rate of this procedure. We aimed to evaluate the effectiveness of preoperative coil localization in VATS wedge resection for sub‐solid lung nodules. Methods From October 2015 to August 2018, 42 patients with 55 sub‐solid lung nodules underwent computed tomography‐guided coil localization with subsequent VATS wedg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…In addition, the wedge resection instead of lobectomy is performed for patients with lung metastasis. [ 10 ] The median blood loss in this study was only 65 mL, which is comparable to that (50 mL) in a previous study regarding of trans-fissural coil localization for sub-fissural LNs. [ 11 ]…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, the wedge resection instead of lobectomy is performed for patients with lung metastasis. [ 10 ] The median blood loss in this study was only 65 mL, which is comparable to that (50 mL) in a previous study regarding of trans-fissural coil localization for sub-fissural LNs. [ 11 ]…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with a prior study that achieved a 91% technical success rate when employing a trans-fissural short hook-wire approach to preoperatively localize LNs. [ 10 ] This result indicated that trans-fissural coil localization for LNs is also technically feasible.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Non-small-cell lung cancer (NSCLC) is the deadliest form of cancer globally [1][2][3], and many patients with earlystage NSCLC can undergo curative surgical resection following tumor detection via chest computed tomography (CT) screening [4][5][6]. Lobectomy with systematic mediastinal lymphadenectomy is the standard approach to treating stage I NSCLC [7][8][9]. However, in many cases, patients are elderly or have a history of comorbidities such as pulmonary dysfunction or atherosclerosis that may preclude their ability to undergo invasive surgical treatment s [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…While sublobar resection (SR) is generally less effective as a curative procedure relative to lobectomy [4], it can better preserve patient pulmonary function [7][8][9]. In stage I NSCLC patients with tumors ≤ 2 cm in size, SR yields similar survival outcomes to lobectomy [5,6].…”
Section: Introductionmentioning
confidence: 99%